Daig kayo ng lola ko a media framing analysis of Lola Gaming stories in mainstream, game press, and broadcast media - Mariano, Aedrian Josef Fernando
The image of a gamer has traditionally been associated with someone young and male, influenced by various forces within the gaming industry and perpetuated by mainstream and games press media. For marginalized gamers, media has often been a site of struggle due to its history of misrepresenting players outside this archetype. This paper examines how Philippine media portrays older gamers through a framing analysis of written and broadcast media stories on Filipina gamer-streamer Lola Gaming. Findings revealed that Lola Gaming was consistently portrayed as a multifaceted figure. Whether in media stories by mainstream or games press media, her portrayal remained consistent. Her characterization highlighted her as a passionate gamer, a humble beginner, a positive adult influence, young-at-heart, and the quintessential Lola. Additionally, media narratives focused on four recurring themes: her finding support and recognition within the gaming community; the role of her grandchildren as warm experts; her encounters with in-game toxicity and discrimination; and gaming as a tool for active aging. Lola Gaming’s media representation is both nuanced and dynamic, presenting her as an older gamer whose portrayal goes beyond restrictive negative stereotypes and highlights her layered identity within the gaming landscape.